LATIHAN KELINCAHAN DAN KETERAMPILAN MENGGIRING BOLA PADA PERMAINAN SEPAK BOLA - Jayadi, Wahyu; Sukamto, Anto; Hasbunallah, Hasbunallah (Indonesian Journal of Educational Studies, 2015)
This experimental study aimed at finding out the effect agility training of both half circle  and center circle models, and then the different effect both agility training model toward dribbling skill at football games. The research was carried out at Faculty of Sport Science State University of Macassar. This research included kind of experimental research, and used randomized group pretest posttest design. Sample consisted of 40 students who were divided into two groups with maching ordinal pairing techniques. The data are colected by using dribbling test at football games. The analyzing techniques of data were uji-t. The result of this research pointed that: 1) the agility training of half circle model was given effect that significance toward dribbling skill at football games;  2) the agility training of center circle model was given effect that significance toward dribbling skill at football games; 3) the result of  agility training of half circle model  was more effective used in teaching  dribbling skill at football games than those using agility training of center ciecle.